2023
DOI: 10.1021/jacsau.3c00421
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable Stimuli-Responsive Ubiquitin Probe for Time-Resolved Monitoring of Substrate Ubiquitination in Live Cells

Lu-Jun Liang,
Yu Wang,
Xiao Hua
et al.

Abstract: Dynamic monitoring of intracellular ubiquitin (Ub) conjugates is instrumental to understanding the Ub regulatory machinery. Although many biochemical approaches have been developed to characterize protein ubiquitination, chemical tools capable of temporal resolution probing of ubiquitination events remain to be developed. Here, we report the development of the first cell-permeable and stimuli-responsive Ub probe and its application for the temporal resolution profiling of ubiquitinated substrates in live cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A robust synthetic method was established for the accelerated manual synthesis of LTX-315-derived peptides and hybrid peptides. Previous studies indicated that the DIC/Oxyma condensation system, which featured high condensation efficiency and low risk of explosion, exhibited significant potency to inhibit side reactions represented by the racemization. Nevertheless, the DIC/Oxyma-based condensation system was mostly conducted at 70 °C or even higher temperatures, which may induce burns to operators and instrument damage. Using our previously established DIC/Oxyma-based strategy under moderate condensation conditions, the peptides were efficiently synthesized in a normal constant-temperature shaker at 50 °C (Figure A). Meanwhile, to attach the CPT, the CPT was first reacted with succinic anhydride, affording the CPT-COOH with the isolated yield of 73.4% and the RP-HPLC purity above 95% (Figures B, S26, and S27). The HATU/HOAt/DIEA system was applied for the condensation of N-terminal Abz, AEEA, CPT-COOH, or 7-(diethylamino)­coumarin-3-carboxylic acid at 28 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A robust synthetic method was established for the accelerated manual synthesis of LTX-315-derived peptides and hybrid peptides. Previous studies indicated that the DIC/Oxyma condensation system, which featured high condensation efficiency and low risk of explosion, exhibited significant potency to inhibit side reactions represented by the racemization. Nevertheless, the DIC/Oxyma-based condensation system was mostly conducted at 70 °C or even higher temperatures, which may induce burns to operators and instrument damage. Using our previously established DIC/Oxyma-based strategy under moderate condensation conditions, the peptides were efficiently synthesized in a normal constant-temperature shaker at 50 °C (Figure A). Meanwhile, to attach the CPT, the CPT was first reacted with succinic anhydride, affording the CPT-COOH with the isolated yield of 73.4% and the RP-HPLC purity above 95% (Figures B, S26, and S27). The HATU/HOAt/DIEA system was applied for the condensation of N-terminal Abz, AEEA, CPT-COOH, or 7-(diethylamino)­coumarin-3-carboxylic acid at 28 °C.…”
Section: Resultsmentioning
confidence: 99%